'We were not planning on this, but …': Adoptive parents' reactions and adaptations to unmet expectations. (5th March 2015) - Moyer, April M.; Goldberg, Abbie E.
Abstract: This study explored adoptive parents' responses to unexpected characteristics of their children with a lens of family stress theory. Ninety individuals in 45 couples, 30 of whom adopted via child welfare and 15 of whom adopted via private domestic adoption, were interviewed 3 months post‐adoptive placement regarding unfulfilled expectations about their child's age, gender, race and special needs. Unmet expectations were especially stressful when parents lacked support and when they perceived themselves as having little power to 'mould' their children. In contrast, perceptions of adequate support and cognitive flexibility appeared to facilitate positive experiences during parents' transition to adoptive parenthood. Implications for professionals are discussed, including suggestions for pre‐adoption training and provision of post‐adoption support.